The Effect of Gratitude Journaling on Depressive Symptoms among University Students - Dewanto, Aji Cokro (Arus Jurnal Pendidikan, 2025)
Depression among university students has emerged as a prominent mental health concern, frequently compounded by academic pressures, social transitions, and emotional distress. The present study examined the effect of a brief gratitude journaling intervention on depressive symptoms among Indonesian university students. A quasi-experimental non-equivalent control group design was employed, with ten nursing students aged 17–21 years being assigned to either an experimental group, comprising five participants, or a control group, comprising five participants. The experimental group was tasked with writing three things they were grateful for each night over a period of seven consecutive days, while the control group received no intervention. The severity of depressive symptoms was measured using the Patient Health Questionnaire-9 (PHQ-9) before and after the intervention. The Wilcoxon signed-rank test revealed a significant reduction in depressive symptoms in the experimental group (Z = –2.032, p = .042), whereas no significant change occurred in the control group. The Mann–Whitney U test confirmed a significant difference in gain scores between groups (U = 0.000, p = .009), with a large effect size (r = .83). These findings suggest that gratitude journaling is an effective intervention for reducing depressive symptoms, even when implemented over a brief period. The study emphasizes the potential of gratitude-based interventions as cost-effective and culturally adaptable strategies to promote emotional well-being in higher education contexts.